Missense mutation in DISC1 C-terminal coiled-coil has GSK3β signaling and sex-dependent behavioral effects in mice - Dachtler, James (Sci Rep, 2016)
Disrupted-in-Schizophrenia 1 (DISC1) is a risk factor for schizophrenia and affective disorders. The full-length DISC1 protein consists of an N-terminal ‘head’ domain and a C-terminal tail domain that contains several predicted coiled-coils, structural motifs involved in protein-protein interactions. To probe the in vivo effects of missense mutation of DISC1’s C-terminal tail, we tested mice carrying mutation D453G within a predicted α-helical coiled-coil region. We report that, relative to wild-type littermates, female DISC1(D453G) mice exhibited novelty-induced hyperlocomotion, an anxiogenic profile in the elevated plus-maze and open field tests, and reduced social exploration of unfamiliar mice. Male DISC1(D453G) mice displayed a deficit in passive avoidance, while neither males nor females exhibited any impairment in startle reactivity or prepulse inhibition. Whole brain homogenates showed normal levels of DISC1 protein, but decreased binding of DISC1 to GSK3β, decreased phospho-inhibition of GSK3β at serine 9, and decreased levels of β-catenin in DISC1(D453G) mice of either sex. Interrupted GSK3β signaling may thus be part of the mechanism underlying the behavioral phenotype associated with D453G, in common with the previously described N-terminal domain mutations Q31L and L100P in mice, and the schizophrenia risk-conferring variant R264Q in humans.